Cooling Energy and Climate Change Nexus in Arid Climate and the Role of Energy Transition - Ammar M. Khourchid; Tareq A. Al-Ansari; Sami G. Al-Ghamdi (Buildings, 2023)
Buildings are significant contributors to climate change through their energy consumption, particularly in countries with hot and dry climates where cooling services require substantial amounts of energy. Climate change is expected to increase cooling demand, further exacerbating the problem. This study investigates the impact of climate change on cooling demands in different building types in Qatar and evaluates related environmental impacts. Using a high-resolution regional climate model, future climate data were obtained for 2071 and 2100 under the Representative Concentration Pathway (RCP) 4.5. The energy consumption of eight prototype buildings was simulated under baseline and future climates, and the environmental impacts were assessed using Life Cycle Assessment (LCA) for natural gas and solar power as energy sources. The study found that the cooling demand could increase by 13–53% and 19–67% in 2071 and 2100, respectively, with buildings having higher thermal insulation and lower window-to-wall ratio being less affected by climate change. The LCA results showed that replacing natural gas with solar power can reduce cooling energy-associated CO2 emissions by 92%. However, challenges such as human toxicity and metal depletion need to be addressed. The study highlights the importance of considering potential climate change scenarios to develop more resilient buildings and encourages implementing efficient recycling and waste management strategies before implementing PV panels.